Efficacy and Safety of Xueshuantong Injection on Acute Cerebral Infarction: Clinical Evidence and GRADE Assessment - Jian Lyu; Yanming Xie; Menghua Sun; Lidan Zhang (Frontiers Media S.A., 2020)
IntroductionXueshuantong injection (XST), a Chinese Medicine, is clinically effective in treating acute cerebral infarction (ACI). However, the meta-analysis of XST combined with conventional treatments (CTs) on ACI remain unexplored. The purpose of this study is to investigate the efficacy and safety of XST combined with CTs on patients with ACI.MethodsRandomized controlled trials (RCTs) were screened from the Cochrane Library, PubMed, Web of Science, EMBASE, and four Chinese medical databases. The meta-analysis was performed using RevMan 5.3 and STATA 16.0. The GRADE assessment was performed by the GRADEprofiler (GRADEpro version: 3.6). The aggregate 95% confidence intervals (CIs) and relative risk (RR) estimates were calculated.ResultsForty studies were included, involving a total of 3,868 patients. XST combined with CTs performed significantly better than CTs alone on the overall response rate (ORR) after treatment (RR = 1.21, 95% CI = 1.17−1.25, P < 0.001). There was no statistical differences in the incidence of adverse reactions between the experimental group (XST plus CTs) and control group (CTs alone). Groups treated with XST substantially decreased the National Institutes of Health Stroke Scale (NIHSS) score compared to the groups without XST (WMD = −5.31, 95% CI = −6.40 to −4.22, P < 0.001). Activities of daily living (ADL) scores were significantly better in the group treated with XST than CTs alone (WMD = 12.51, 95% CI = 5.6−19.38, P < 0.001). Patients who received XST combined with CTs showed significantly higher improvements in high-sensitivity C-reactive protein (hs-CRP) (WMD = −2.47, 95% CI = −3.11 to −1.82, P < 0.001) and interleukin 6 (IL-6) (WMD = −13.66, 95% CI = −17.80 to −9.51, P < 0.001) than those who received CTs alone. The GRADE assessment indicates that the comprehensive quality of this evidence is low.ConclusionsThis meta-analysis and GRADE assessment conditionally recommend that XST combined with CTs can increase the overall response rate, ameliorate neurological deficit, and improve activities of daily living function more than CTs alone. A significant reduction in the hs-CRP and IL-6 levels were observed when XST was combined with CTs.